Telephone Call Duration Measurement Reference System - Kaskonas, P.; Meskuotiene, A. (Elektronika ir Elektrotechnika, 2014)
The problems about telecommunication networks call duration measurement equipment validation and verification procedures are discussed in the paper. Because the maximum permissible error of network’s call duration measurement system comprises many error terms that depend on telecommunication network structure, technology, call processing, etc., the “end–to-end” testing procedure have to be used. Therefore special reference system providing traceability of time measurements in telecommunications and measuring the duration of the test calls independent of network’s equipment, utilizing “end-to-end” measurement principle, was developed. The structure and operation principles of the reference system are presented in details in the paper. Evaluated call duration measurement expanded uncertainty and systematic correction of the developed reference system is less than 0.1 s. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.3773